An investigation of the repairability of ferrocement - Adajar, Jose Caringal (1989)
Ferrocement is known to have an advantage over the building materials in that it can be repaired efficiently. One matter that is not quite clear, however, involves the question on how much of the original strength of a ferrocement element could be recovered after the repair. To address this, three types of loading were tested in the following experimental study. These were compression, tension, and flexure. For each type, the mixture of the constituent materials was varied into 1:2 45%, 1:2.5, 50% and 1.3 55% (cement : sand water cement ration by weight). for every mixture, the number of layers of wire mesh was also varied into two layers, 4 layers, and 5 layers. A total of one hundred and sixty-two ferrocement specimens were used in this investigation, with fifty-four each for compression, tension and flexure.